Reliability of two-dimensional kinematic assessment of single-leg landing, countermovement jump, and broad jump techniques among elite handball players - Ribic, A.; Spudic, D.; Šarabon, N.; Pori, P. (Kinesiologia Slovenica, 2025)
The aims of this study were: a) to assess the intra-session reliability of two-dimensional kinematic variables related to the knee, hip, and trunk joints, and b) to compare the results between subjectively and objectively identified key movement positions in single-leg countermovement jumps (SLCMJ), broad jumps (SLBJ), and drop landings. Eighty elite handball players (mean age 21.8 years; weight 92.0 kg; height 1.9 m) participated in the study. Three repetitions of each test, using both the dominant and nondominant legs, were video recorded from lateral and frontal planes. Kinematic analysis was performed manually using Kinovea software. Inclinations of the shin, thigh, pelvis, and trunk (absolute variables) were calculated based on anatomical landmarks, along with joint angles (relative variables). Key movement positions were identified subjectively by expert assessment and objectively by the time point of the highest vertical ground reaction force for each task. The results indicated moderate-excellent reliability for drop landing test (ICC2.1 = 0.54-0.99), moderate-good reliability (ICC2.1 = 0.51- 0.83) for SLCMJ, and poor-moderate reliability for SLBJ in both the push off (ICC2.1 = 0.01-0.81) and landing phases (ICC2.1 = 0.10-0.86). Significant differences were found between the results from subjective and objective key movement position identification (p < 0.05). Based on the results, we recommend conducting at least three test repetitions and averaging the outcomes to ensure reliability when performing manual 2D kinematic analysis with manual marker placement, as well as maintaining consistency in the criteria used to determine key movement positions for variable extraction.